THE USE OF COMMUNICATION MEDIA IN THE TEACHING AND LEARNING PROCESS AT UNIVERSITIES IN ACEH DURING THE COVID-19 PANDEMIC - Juliani, Reni; Maulina, Putri; Juliana, Rena (SOURCE : Jurnal Ilmu Komunikasi, 2021)
Covid 19 cases in Indonesia have been published since early March 2020. These cases have continued to increase significantly, spreading to almost all provinces in Indonesia including Aceh Province. In fact, Aceh province is the province with the highest increase in coronavirus deaths in mid-October. As conditions deteriorate, the government continues to implement policy reforms to suppress the spread of Covid-19, including policies in the education world using online methods. Online learning is an educational innovation that uses elements of information technology as a means of support. This study aims to answer the question, how do online communication and learning at universities in Aceh during the Covid-19 pandemic? The theory used in this research is the theory of technological determinism. This research uses qualitative methods with descriptive analytical presentation. The research showed that Aceh universities used many online learning models such as the Zoom application, Google Classroom, WhatsApp and others. This is related to the interest of the application users. Online learning guidelines also have advantages and disadvantages with students and lecturers studying at universities in Aceh.